Multidisciplinary team care in pituitary tumours - Marques, Pedro (2024)
The optimal care for patients with pituitary tumours is best provided in a multidisciplinary and collaborative environment, which requires the contribution of multiple medical specialties working together. The benefits and advantages of the pituitary multidisciplinary team (MDT) are broad, and all relevant international consensus and guidelines in the field recommend that patients with pituitary tumours should always be managed in a MDT. Endocrinologists and neurosurgeons are normally the leading specialties within the pituitary MDT, supported by many other specialties with significant contributions to the diagnosis and management of pituitary tumours, including neuropathology, neuroradiology, neuro-ophthalmology, and otorhinolaryngology, among others. Here, we review the literature concerning the concepts of Pituitary MDT/Pituitary Tumour Centre of Excellence (PTCOE) in terms of their mission, goals, benefits, structure, proposed models of function, and barriers, and we also provide the views of different specialists involved in our Pituitary MDT.